Zatoichi and the Chess Expert Based on a Short Story by Kan Shimozawa - Misumi, Kenji; Makiura, Chishi; Katsu, Shintaro; Narita, Mikio; Hayashi, Chizu (Criterion, 2019)
Kenji Misumi, who directed the first installment of the Zatoichi series, returns with this tale in which the blind swordsman once again finds himself the protector of a child: a little girl pursued by both devious family members and bloodthirsty ruffians. Further complicating his journey is a new acquaintance - a tremendously skilled chess player (the charismatic Mikio Narita) who has mysterious motivations and a dark past. [www.criterion.com]
Keywords: Blu-Ray-Disc